THE APPLICATION OF « NEMO » ARTIFICIAL INTELEGENCE IN ARABIC LANGUAGE LEARNING IN THE 4.0 REVOLUTION ERA AT AL- KHALIFAH ISLAMIC BOARDING SCHOOL CIBUBUR - Abu Bakar Shiddiq (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Abstract Android application-based learning media is an effective way, because the students motivation have increased in learning and practicing learning activities. Learning media which utilizes Android which emphasizes on several applications that are easily owned by all students and instructors, so that they are easy and affordable. Gagne and Briggs in the Book (Azhar, 2002) provide a limitation on the scope of the media including physical devices with the aim of conveying subject matter such as books, tape recorders, video recorders, films, slides (picture frames), photos, graphics, television and computer. Nemo is an android application that is designed as a medium of learning and language learning by mastering a number of useful words. In the android application, Nemo is like a simple pocket dictionary so that it helps in improving the language level through various learning materials. This study examines the effectiveness of the use of Android-based Arabic Nemo teaching materials for students at Al- Khalifah Islamic boarding school Cibubur. Beginner level students at Al- Khalifah Islamic boarding school Cibubur in learning Arabic. Many relevant studies prove that the teaching and learning activities using android made learning outcomes better than teaching and learning activities without using it. This study aims to test the effectiveness of instructional media on learning outcomes and whether it is more effective than teaching and learning activities that do not use instructional media in Arabic learning, the average value obtained indicates the benefits and effectiveness of using NEMO media on success in teaching and learning activities.